Pengaruh Motivasi Berprestasi dan Persepsi Siswa Tentang Cara Guru Mengajar Terhadap Hasil Belajar Matematika Siswa - Wulandari Wulandari; Syahrul Azmi; Nani Kurniati; Nurul Hikmah (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to: (1) find out how achievement motivation affects the mathematics learning outcomes; (2) knowing how the influence by student perceptions of how teachers teach on mathematics learning outcomes; and (3) to find out how the influence of achievement motivation and student perceptions about how teachers teach on the mathematics learning outcomes at VIII grade students of SMPN 16 Mataram in academic year 2019/2020. This type of research is ex post facto research. The population of this study were all students at VIII grade as many as 110 students consisting of classes A, B, C and D. The sample used was saturated sampling where the entire population was the sample in this study. The data collection technique used was a questionnaire and tests. This research uses prerequisite test analysis techniques and inferential analysis techniques. The results obtained show: (a) There is a significant effect of achievement motivation on the mathematics learning outcomes with a contribution of 10.1%; (b) there is a significant influence on student perceptions of how teachers teach on mathematics learning outcomes with a contribution of 17.8%; and (c) there is a significant influence on achievement motivation and student perceptions of how teachers teach on mathematics learning outcomes with a contribution of 20.1%.